DESAIN TATA DISPLAY PASAR BUAH SEBAGAI DAYA TARIK WISATA BELANJA DI PASAR GEDHE HARDJONAGORO - Ariyanto, Ahmad Fajar; Mahendrapati, Alexander Nawangseto (Acintya, 2017)
Traditional market in Surakarta is still preserved and being part of economic activity of the society,despite the increasing number of supermarkets. The revitalization of these markets is one of the medium-term development plans of Surakarta because compared to the other sources, traditional markets make the biggest contribution to the local government revenue. One of these markets is thewestern part of Pasar Gedhe Hardjonagoro whose commodities are fresh fruits. Unfortunately, therehabilitation and renovation programs are only focused on the main building. The inside area wherethe trade activities between sellers and buyers happen is excluded from the rehabilitation program.Considering Pasar Gedhe as a tourist destination, the needs of market management especially fordisplaying the product is essential to attract the consumers and tourists. This article is the result of anapplied research in interior design about the design of display system of fruit sellers in the westernpart of Pasar Gedhe Hardjonagoro in Surakarta. This applied research is a qualitative descriptiveanalysis with case study approach. The work employs functional, ergonomic, thematic, and stylishapproaches for the design solution. The result acquired from the interior design research is a zoningwhich is divided into selling, circulation and service, outdoor zone, and managing the circulation andtwo-side services, and creating the interior theme. While the result on the display design is the designneeds to be able to functionally support the trade activities, easy to maintenance, solid, long-lasting,safe, the display system represents the locality, and how the commodities can be an interesting visualattraction. The display system is designed to be an open layout system so that it creates a sociocultural interaction for the people within the market.Keywords: Pasar Gedhe rehabilitation, zoning, display system, functionality, visual attraction.